DOCTRINAL RULES-MAKING OF MILITARY ADMINISTRATION BODIES: LEGAL ASPECTS OF VALIDATION - Shulgin, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article analyzes the legal (organizational-theoretical, comparative-applied, temporal-terminological, legitimation, validation aspects of the process of doctrinal rule-making of the military administration of the Armed Forces of Ukraine in the field of combat training and application of the Armed Forces of Ukraine and other components of the Ukrainian Defense Forces. importance on the way to the Euro-Atlantic integration of our country, for the effective operation of national joint defense forces in a special period, the preparation of units of the Armed Forces of Ukraine for joint action and interoperability with the armed forces of NATO member states. In order to form a balanced system-scientific approach to streamlining the doctrinal rule-making process of the military administration of the Armed Forces of Ukraine, an attempt was made to explore the nature, legal features of adaptation, validation and place of military publications in the national system of military administration, including doctrinal documents borrowed from member states. NATO. This is also relevant in view of the fact that the doctrine was perceived in the system of military law of Ukraine exclusively as a military-political act of the national level. It is necessary to harmonize normative-legal and doctrinal-conceptual acts of military administration of Ukraine both on the basis of their legal force in the system of normative legal acts of military legislation and taking into account their hierarchy on the basis of organizational and operational level (strategic, operational, tactical). The state of legal support of doctrinal rule-making within the framework of the Defense Forces of Ukraine and military-departmental doctrinal rule-making has been clarified. The legal essence and nature of military publications, in particular doctrines in the system of military management, their general and special concept taking into account existing problems and features of modern process of normative-legal regulation, military-departmental law enforcement, transformation of legal understanding of hierarchy of military management acts taking into account military implementation are established and substantiated. -operative doctrines, amendments to the system of national defense and military management. Proposals have been formulated in order to optimize the process of doctrinal rule-making of military administration bodies, adaptation, validation and determination of the place of military-administrative operational doctrines in the system of acts of military administration of the Armed Forces of Ukraine.
Keywords: military publications, doctrinal documents, sources of military law, system of military management acts, defense forces, militarylegal relations, military legislation, doctrinal standards of NATO member states, adaptation to NATO standards, validation, legitimacy, militarylegal acculturation